A pilot study to determine levels of diabetes knowledge among health care workers in nursing homes. Issue 1 (27th February 2013) - Smide, Bibbi; Nygren, Ulla
Abstract Health care workers employed in nursing homes need sufficient diabetes knowledge to make adequate decisions in order to optimise diabetes management and minimise complications which may arise from poor diabetes control. The aim of this study was to determine levels of diabetes knowledge among health care workers when presented with a case description regarding an older person. Ten health care workers were asked to read a paper copy of the case description, reflect upon it and express their understanding of the case in question. The main results were summarised in two categories: namely, diabetes knowledge in relation to the presented case description and general diabetes knowledge. Some of the respondents considered the symptoms to be related to hyperglycaemia, while others were uncertain. Health care workers' general diabetes knowledge varied. In order to optimise diabetes management and minimise complications, health care workers' knowledge gaps in diabetes need to be reduced through regular diabetes education. Copyright © 2013 FEND. Published by John Wiley & Sons, Ltd.